Effect of telephone calls and text message reminder interventions on the adherence to antiretroviral drugs among HIV/AIDS clients receiving care in Sokoto state, Nigeria - Oladigbolu, Remi A.; Oche, Mansur O.; Raji, Mansur O.; Gana, Godwin J.; Ezenwoko, Zainab A. (International Journal Of Community Medicine And Public Health, 2020)
Background: Adherence to antiretroviral therapy (ART) has been proven to be a good predictor of clinical outcome among patients on ART. This study aimed to assess the effect of phone reminder interventions on the knowledge of Human immunodeficiency syndrome (HIV)/ Acquired immunodeficiency syndrome (AIDS), ART and adherence to ART drugs among non-adherent patients receiving care in Sokoto State. Methods: A quasi-experimental study was conducted among 196 non-adherent HIV patients between February and July 2017. The intervention group received monthly telephone calls and weekly text messages for twelve weeks while the control group received only standard of care. Self-report adherence, forgetfulness to take ART and knowledge of HIV/AIDS and ART were measured pre- and post- intervention. Data were processed and analysed using IBM Statistical package for social sciences (SPSS) version 22 computer statistical software package. Results: At baseline, although majority of participants in both groups had good knowledge of HIV/AIDS, ART drug adherence, they were both non-adherent to ART and it was mainly due to forgetfulness. At post intervention, respondents with good knowledge and adherent to ART were significantly higher in the intervention group. There was also a significantly lower proportion of forgetfulness among the intervention group compared with control group (c2=47.57, p<0.001). Conclusion: The interventions were found to be effective. The Federal Ministry of Health (FMoH) with the support of implementing partners need to integrate these interventions into clinical setting as part of comprehensive care for HIV care and treatment to assist in improving their knowledge of HIV/AIDS, ART and adherence to ART.